Peripheral spectrum neurological disorder after arbovirus infection is associated with HLA-F variants among Northeastern Brazilians - Sonon, Paulin; Collares, Cristhianna V.A.; Ferreira, Maria Lúcia Brito; Almeida, Renata Santos; Sadissou, Ibrahim; Cordeiro, Marli Tenório; de Fátima Militão de Albuquerque, Maria; Castelli, Erick C. [UNESP]; Lucena-Silva, Norma; Donadi, Eduardo A. (Elsevier, 2021)
Introduction: Non-classical class I human leukocyte antigens (HLA) molecules are known to modulate the function of cytotoxic cells (NK and T CD8+) during viral infection by interacting with inhibitory/activating receptors. However, little is known about the HLA-E/-F genetic variability on arbovirus infections. Methods: We evaluated by massive parallel sequencing the full HLA-E/-F genetic diversity among patients infected during the arbovirus (ZIKV, DENV, and CHIKV) outbreak leading to a broad range of neurological complications in the Brazilian State of Pernambuco. In parallel, healthy blood donors from the same area were also studied. Plink and R software were used for genetic association study. To limit the false-positive results and enhance the reliability of the results, we adopted P-values <0.01 as significant levels. Results: Compared to controls, the HLA-F alleles: −1610 C (rs17875375), +1383 G (rs17178385), and +3537 A (rs17875384), all in complete linkage disequilibrium with each other (r2 = 1), were overrepresented in patients presenting peripheral spectrum disorders (PSD). The HLA-F*Distal-D haplotype that harbored the −1610 C allele exhibited a trend increase in PSD group. No associations were found for HLA-E. Conclusions: Our findings showed that the HLA-F genetic background seems to be more important than HLA-E on the susceptibility to PSD complications.
Keywords: Arbovirus; ESD; HLA-E; HLA-F; Pernambuco; PSD